2018
DOI: 10.1371/journal.pone.0203290
|View full text |Cite
|
Sign up to set email alerts
|

Failure to detect functional transfer of active K-Ras protein from extracellular vesicles into recipient cells in culture

Abstract: Exosomes, extracellular nanovesicles that carry nucleic acids, lipids, and proteins, have been the subject of several studies to assess their ability to transfer functional cargoes to cells. We recently characterized extracellular nanovesicles released from glioblastoma cells that carry active Ras in complex with proteins regulating exosome biogenesis. Here, we investigated whether a functional transfer of Ras from exosomes to other cells can initiate intercellular signaling. We observed that treatment of seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 79 publications
0
6
0
Order By: Relevance
“… [ 155 ] CLIC1 Up GFP, FLAG-tagged CLIC1 is a circulating protein, secreted via extracellular vehicles (Evs) released by either cell lines or GBM-derived CSCs. [ 156 ] K-Ras Up Raf-RBD [ 157 ] immunoglobulin (Ig) G2 and IgG4 Up CD163 [ 158 ] TrkB Up YKL-40 Inhibits tumor growth in vivo. Plays a key role in the control of GBM progression and aggressiveness.…”
Section: Exosomal Micrornas and Gliomasmentioning
confidence: 99%
See 1 more Smart Citation
“… [ 155 ] CLIC1 Up GFP, FLAG-tagged CLIC1 is a circulating protein, secreted via extracellular vehicles (Evs) released by either cell lines or GBM-derived CSCs. [ 156 ] K-Ras Up Raf-RBD [ 157 ] immunoglobulin (Ig) G2 and IgG4 Up CD163 [ 158 ] TrkB Up YKL-40 Inhibits tumor growth in vivo. Plays a key role in the control of GBM progression and aggressiveness.…”
Section: Exosomal Micrornas and Gliomasmentioning
confidence: 99%
“…Tumor-derived proteins that are freely circulating in blood may be highly diluted, and could be mixed with other similar circulating biomolecules, which could confuse the tests [ 177 , 178 ]. It was found that many exosomal proteins such as HMGB 1[ 140 ], IL-8, PDGFs, caveolin 1, and lysyl oxidase [ 141 ], L1CAM [ 142 ], STC1, STC2 [ 143 ], EGFRvIII [ 144 ], VEGF-A [ 145 ], CRYAB [ 146 ], PTRF [ 147 ], PD- 1[ 148 ], IL13Rα2, IL13QD [ 149 ], CAV 1 [ 150 ], NK-Exo [ 151 ], SRSF1, SRSF3 [ 152 ], NANOGP8 [ 153 ], PTENP1 [ 155 ], CLIC1 [ 156 ], K-Ras [ 157 ], immunoglobulin (Ig) G2 and IgG4 [ 158 ], TrkB [ 159 ], MGMT mRNA [ 160 ], EGFRvIII [ 161 ], N-glycoproteins [ 162 ], LOX, ADAMTS1, TSP1, VEGF [ 163 ], NF-κB [ 165 ], Glut-1, HK-2, and PKM-2 [ 166 ], TDP-43 [ 167 ] were up-regulated. On the other hand some other proteins, such as IL-8, ZAP70, TGF-β [ 148 ], IFN-gamma, granzyme B [ 154 ], and CRCL [ 164 ] were down-regulated in glioma tumors (Table 2 ).…”
Section: Exosomal Proteins In Gliomamentioning
confidence: 99%
“…[ 15,18 ] Although CRE recombinase has an efficiency of 55%, [ 19 ] horizontal transfer was shown to happen mainly between tumor cells in vivo, but not between tumor cells and host cells. [ 15,18 ] These results have been further confirmed using other genetic strategies, [ 20,21 ] suggesting that surface binding may represent the main mechanism of EV‐mediated tumor–host communications in vivo.…”
Section: Introductionmentioning
confidence: 71%
“…We reported an increase in the TP53 copy number in LPSderived exosomes, suggesting that the mechanism behind DNA sorting is not stochastic. Of note, it has recently been shown that functional KRAS protein transfer from cell to cell is an extremely rare event [29]. To date, the mechanisms by which nucleic acids are sorted and packaged within EVs have yet to be elucidated [30].…”
Section: Discussionmentioning
confidence: 99%